Baseline characteristics of the North American prodromal Synucleinopathy cohort. Issue 4 (8th February 2023) - Elliott, Jonathan E.; Lim, Miranda M.; Keil, Allison T.; Postuma, Ronald B.; Pelletier, Amelie; Gagnon, Jean‐François; St. Louis, Erik K.; Forsberg, Leah K.; Fields, Julie A.; Huddleston, Daniel E.; Bliwise, Donald L.; Avidan, Alon Y.; et al.
Abstract: Objective: Rapid eye movement (REM) sleep behavior disorder (RBD) is widely considered a prodromal synucleinopathy, as most with RBD develop overt synucleinopathy within 10 years. Accordingly, RBD offers an opportunity to test potential treatments at the earliest stages of synucleinopathy. The North American Prodromal Synucleinopathy (NAPS) Consortium has created a multisite RBD participant, primarily clinic‐based cohort to better understand characteristics at diagnosis, and in future work, identify predictors of phenoconversion, develop synucleinopathy biomarkers, and enable early stage clinical trial enrollment. Methods: Participants ≥18 years of age with overnight polysomnogram‐confirmed RBD without Parkinson's disease, dementia, multiple system atrophy, or narcolepsy were enrolled from nine sites across North America (8/2018 to 4/2021). Data collection included family/personal history of RBD and standardized assessments of cognitive, motor, sensory, and autonomic function. Results: Outcomes are primarily reported based on sex (361 total: n = 295 male, n = 66 female), and secondarily based on history of antidepressant use ( n = 200 with, n = 154 without; with correction for sex differences) and based on extent of synucleinopathy burden ( n = 56 defined as isolated RBD, n = 305 defined as RBD+ [i.e., exhibiting ≥1 abnormality]). Overall, these participants commonly demonstrated abnormalities in global cognition (MoCA; 38%), motor function (alternate tap test; 48%), sensory (BSIT; 57%), autonomic function (orthostatic hypotension, 38.8%), and anxiety/depression (BAI and PHQ‐9; 39.3% and 31%, respectively). Interpretation: These RBD participants, assessed with extensive history, demographic, cognitive, motor, sensory, and autonomic function demonstrated a lack of sex differences and high frequency of concomitant neurological abnormalities. These participants will be valuable for future longitudinal study and neuroprotective clinical trials.